Exposition of Disgust Rasa in Fitzgerald’s The Great Gatsby - Paudel, Dhaneshwar (Literary Studies, 2023)
This research article makes an attempt to explore the exposition of disgust Rasa in F. Scott Fitzgerald’s The Great Gatsby (1925). Human being has strong negative feeling of aversion or sickening feeling of revulsion because they are attracted to the materialistic life now. They have been money minded and have self-centered ideas. They only want to earn money. Sometime, they do the illegal work for earning money. They have sexual shameless behavior. They are highly obsessive and abominable. They desire to establish the factories for their luxury. They have become totally selfish. So, they have the destructive morality. Moreover, the whole landscape is covered by dust and then, they have complex life and it produces the disgust rasa which represents depression and dissatisfaction. It has a powerful pessimistic affection of disapproval. This study has read the novel through the critical design that Sheldon Pollock has developed the critical concept of disgust rasa. Thus, the finding of the research is that the modern men have no morality and they have Sickening and shocking manner, etc. which product full of disgust rasa in their life.